Capacity and Opportunity: Predicting Engagement for Middle School Students With Behavioral Disorders. (December 2015) - Herron, Marsha Dempsey; Martin, Jim
This study examined the capacity and opportunity scores of 36 middle school students with emotional and behavioral disorders (EBD) on the student version of the American Institutes for Research (AIR) Self-Determination Scale across three school engagement factors: grade point averages (GPA), school absences, and frequency of school disciplinary encounters. Poor grades, school absences, and frequency of disciplinary actions pose academic problems for middle school students with EBD. Three multiple regression models determined the predictive relationships between self-determination Capacity and Opportunity subscale scores and GPA, Absences, and Discipline. Higher capacity and opportunity scores predicted greater student GPA, fewer student absences, and fewer disciplinary encounters for students at school. Results of this study demonstrate the need for increased opportunities at school and home for students with EBD to learn and practice self-determination skills.